Stink and the Great Guinea Pig Express - McDonald, Megan; Reynolds, Peter 1961- (Edina, Minn. : Spotlight, 2010)
Stink Moody, friends Webster and Sophie, and Mrs. Birdwistle visit tourist attractions in Virginia as they try to give away 101 guinea pigs rescued from a laboratory, although Stink is very reluctant to give away his favorite, Astro.
Keywords: Guinea pigs -- Fiction; Animal welfare -- Fiction; Automobile travel -- Fiction; Virginia -- Fiction; Fiction